Descriptive Epidemiological Study of TB Occurrence in Matraman District Health Center Post Covid-19 Pandemic - Alib Birwin; Ahmad Faridi; Mohammad Furqan; Taufik Maryusman; Arif Seytawan (Universitas Aisyah Pringsewu, 2023)
Objective: Tuberculosis (TB) is caused by Mycobacterium tuberculosis bacteria and is transmitted through coughing, sneezing, talking, or spitting. TB cases are more common in men than women and are higher in areas with poor living conditions and low socio-economic status. In 2018, East Java had 56,445 TB cases, with 31,211 cases in men and 25,234 cases in women. Puskesmas Kecamatan Matraman had 630 suspected TB cases in 2020, with 108 confirmed cases and a low TB CDR achievement. Methods: This is a descriptive study aimed at describing the frequency distribution pattern of Tuberculosis (TB) occurrences according to the variables of person, place, and time using a cross-sectional/prevalence study design approach. The study sample consisted of 159 individuals who were Tuberculosis (TB) patients, and the sample was selected using purposive sampling that met the inclusion and exclusion criteria. Results: show the gender and age group of TB patients. The study found that the majority of TB patients at Puskesmas Kecamatan Matraman were male. The proportion of male TB patients ranged from 55.45% to 67.5%, along with other factors such as lifestyle and environment. Most TB patients were in the productive age group of 15-59 years, Conclusion: indicating the need for prevention and control efforts targeted at this group, such as improving knowledge and awareness of TB, promoting healthy lifestyles, and providing accessible and quality health services. Diagnosis of TB patients can be done through microscopic examination or culture. Abstrak: Penyakit TBC disebabkan oleh bakteri Mycobacterium tuberculosis dan ditularkan melalui batuk, bersin, berbicara, atau meludah. Kasus TB lebih sering terjadi pada pria daripada wanita dan lebih tinggi di daerah dengan kondisi hidup yang buruk dan status sosial ekonomi rendah. Pada tahun 2018, Jawa Timur memiliki 56.445 kasus TB, dengan 31.211 kasus pada pria dan 25.234 kasus pada wanita. Puskesmas Kecamatan Matraman memiliki 630 kasus TB yang dicurigai pada tahun 2020, dengan 108 kasus yang terkonfirmasi dan pencapaian CDR TB yang rendah. Studi ini bertujuan untuk menggambarkan epidemiologi deskriptif kasus TB di Puskesmas Kecamatan Matraman setelah COVID-19, dengan fokus pada variabel orang, tempat, dan waktu. Metode penelitian yang digunakan adalah studi deskriptif dengan analisis data sekunder. Hasil penelitian menunjukkan bahwa jenis kelamin dan kelompok usia. Studi ini menemukan bahwa sebagian besar pasien TB di Puskesmas Kecamatan Matraman adalah laki-laki. Proporsi pasien TB laki-laki berkisar antara 55,45% hingga 67,5%, faktor-faktor lain seperti gaya hidup dan lingkungan. Sebagian besar pasien TB berada dalam kelompok usia produktif antara 15-59 tahun, yang menunjukkan perlunya upaya pencegahan dan pengendalian yang ditargetkan pada kelompok ini, seperti meningkatkan pengetahuan dan kesadaran tentang TB, mempromosikan gaya hidup sehat, dan menyediakan layanan kesehatan yang mudah dijangkau dan berkualitas. Diagnosis pasien TB dapat dilakukan melalui pemeriksaan mikroskopis atau kultur.